Shenxiong glucose injection inhibits oxidative stress and apoptosis to ameliorate isoproterenol-induced myocardial ischemia in rats and improve the function of HUVECs exposed to CoCl2 - Wu, Zhong-Xiu; Chen, Shuai-Shuai; Lu, Ding-Yan; Xue, Wei-Na; Sun, Jia; Zheng, Lin; Wang, Yong-Lin; Li, Chun; Li, Yong-Jun; Liu, Ting (Frontiers in Pharmacology, 2023)
Background: Shenxiong Glucose Injection (SGI) is a traditional Chinese medicine formula composed of ligustrazine hydrochloride and Danshen (Radix et rhizoma Salviae miltiorrhizae; Salvia miltiorrhiza Bunge, Lamiaceae). Our previous studies and others have shown that SGI has excellent therapeutic effects on myocardial ischemia (MI). However, the potential mechanisms of action have yet to be elucidated. This study aimed to explore the molecular mechanism of SGI in MI treatment. Methods: Sprague-Dawley rats were treated with isoproterenol (ISO) to establish the MI model. Electrocardiograms, hemodynamic parameters, echocardiograms, reactive oxygen species (ROS) levels, and serum concentrations of cardiac troponin I (cTnI) and cardiac troponin T (cTnT) were analyzed to explore the protective effect of SGI on MI. In addition, a model of oxidative damage and apoptosis in human umbilical vein endothelial cells (HUVECs) was established using CoCl2. Cell viability, Ca2+ concentration, mitochondrial membrane potential (MMP), apoptosis, intracellular ROS, and cell cycle parameters were detected in the HUVEC model. The expression of apoptosis-related proteins (Bcl-2, Caspase-3, PARP, cytoplasmic and mitochondrial Cyt-c and Bax, and p-ERK1/2) was determined by western blotting, and the expression of cleaved caspase-3 was analyzed by immunofluorescence. Results: SGI significantly reduced ROS production and serum concentrations of cTnI and cTnT, reversed ST-segment elevation, and attenuated the deterioration of left ventricular function in ISO-induced MI rats. In vitro, SGI treatment significantly inhibited intracellular ROS overexpression, Ca2+ influx, MMP disruption, and G2/M arrest in the cell cycle. Additionally, SGI treatment markedly upregulated the expression of anti-apoptotic protein Bcl-2 and downregulated the expression of pro-apoptotic proteins p-ERK1/2, mitochondrial Bax, cytoplasmic Cyt-c, cleaved caspase-3, and PARP. Conclusion: SGI could improve MI by inhibiting the oxidative stress and apoptosis signaling pathways. These findings provide evidence to explain the pharmacological action and underlying molecular mechanisms of SGI in the treatment of MI.